Measurment of Web Usability: Web Page of Hacettepe University Department of Information Management - Nazan Özenç Uçak; Tolga Çakmak (Türk Kütüphaneciliği)
Today, information is produced increasingly in electronic form and retrieval of information is provided via web pages. As a result of the rise of the number of web pages, many of them seem to comprise similar contents but different designs. In this respect, presenting information over the web pages according to user expectations and specifications is important in terms of effective usage of information. This study provides an insight about web usability studies that are executed for measuring effectiveness of web pages in design and usage sections. It also puts emphasis on the usability study of Hacettepe University, Department of Information Management web page. Seven volunteered users are determined from different levels. Qualitative and quantitative methods were used together for usability study. This usability study consists of three stages. In the first stage, “pre-test” was implemented for determining users ’ general computer and Internet skills. In the second stage, “classical usability study” was implemented. Fourteen questions that require the usage of the web page were prepared and directed to users. Clicking number and retrieval time was recorded and think-aloud protocol was also implemented during the study. In the third stage, a final test was implemented to users in order to find out the ideas of users about Hacettepe University, Department of Information Management web page. As a result of the usability study, positive and negative features of the web page were determined by the analyses of qualitative and quantitative data. Finally the results that were elaborated from the analyses have been used for revision that will provide an effective usage of the web page.